Pengaruh model pembelajaran student team achievment divisions (STAD) dan motivasi belajar terhadap kemampuan menulis puisi pada siswa kelas V sekolah dasar - Ernawati Ambarningrum; St. Y. Slamet; Karsono Karsono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This research aimed to identify differences in the ability to write poetry in grade 5th students who are taught using STAD learning model with 5th grade students who are taught using NHT learning model, identify the differences in writing poetry skill of 5th grade students who have high and low learning motivation, identify the interaction of learning models and learning motivation with poetry writing skills. This research is Quantitative Research with Factorial Design. The research subjects were 25 fifth-grade students of SDN Purwotomo in the 2018/2019 academic year. The data were collected with essay test and non test (Questionnaire). They were analysed using prerequisite test analysis. There is a difference in the poetry writing ability of students taught with STAD learning model and students taught using NHT learning model indicated by FA = = 12,63 > Ftable = 4,08, there is difference in the poetry writing ability of students who have high learning motivation with students who have low learning motivation indicated by FB = 15,29 > Ftable = 4,08, there is an  interaction between learning model and learning motivation towards poetry writing ability indicated by FAB = 12,82> Ftable =4,08.